Evolution of defences in large tropical plant genera: perspectives for exploring insect diversity in a tri-trophic context - Volf, Martin; Salminen, Juha-Pekka; Segar, Simon T (Current opinion in insect science, 2019)
Divergence and escalation in defences promote chemical diversity in plants, and consequently the diversity of insect herbivores. This diversification cascades to insect parasitoids through direct effects on host herbivore susceptibility, changes in herbivore community composition, or disparity in plant volatiles. Large tropical plant genera represent an ideal model for studying these trends due to the high diversity of sympatric species and their insects. Novel measures of chemical structural similarity should be used to analyse evolutionary trends in both direct and indirect defences. Host chemical data need to be combined with detailed herbivore and parasitoid data. This will help to identify truly active compounds. Furthermore, resolved genomic phylogenies for plants and insects should be included to assign directionality in the processes.
Keywords: Biodiversity; rostliny; Animals; Herbivory; hmyz; biologická evoluce; Insecta; Plants; zvířata; Biological Evolution; tropické klima; biodiverzita; Tropical Climate; potravní řetězec; Food Chain; býložravci